2014
DOI: 10.1002/asi.23239
|View full text |Cite
|
Sign up to set email alerts
|

How is research blogged? A content analysis approach

Abstract: Blogs that cite academic articles have emerged as a potential source of alternative impact metrics for the visibility of the blogged articles. Nevertheless, to evaluate more fully the value of blog citations, it is necessary to investigate whether research blogs focus on particular types of articles or give new perspectives on scientific discourse. Therefore, we studied the characteristics of peer-reviewed references in blogs and the typical content of blog posts to gain insight into bloggers' motivations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 30 publications
(101 reference statements)
3
30
1
Order By: Relevance
“…This supports the idea that Mendeley readership could be useful for the analysis and evaluation of these document types, especially given that most of them are traditionally excluded from citation analysis (Waltman et al, 2011) due to their lower citation frequency. The popularity of these other document types has been reported for other altmetrics, particularly for Twitter (Haustein et al, 2015) and research blogs (Schema, Bar-Ilan, & Thelwall, 2015). This stronger presence of other document types in Mendeley also suggests that Mendeley readership may capture a mix of citation and social media patterns, since documents with different relevance for citations and social media are reasonably saved in Mendeley (e.g.…”
Section: Discussionmentioning
confidence: 77%
“…This supports the idea that Mendeley readership could be useful for the analysis and evaluation of these document types, especially given that most of them are traditionally excluded from citation analysis (Waltman et al, 2011) due to their lower citation frequency. The popularity of these other document types has been reported for other altmetrics, particularly for Twitter (Haustein et al, 2015) and research blogs (Schema, Bar-Ilan, & Thelwall, 2015). This stronger presence of other document types in Mendeley also suggests that Mendeley readership may capture a mix of citation and social media patterns, since documents with different relevance for citations and social media are reasonably saved in Mendeley (e.g.…”
Section: Discussionmentioning
confidence: 77%
“…There were also 150 cases where blog posts and cited articles were both from the same year. 13.7% of articles cited in blogs were at least 14 years old (this figure was 7% for health blogs (Shema, Bar-Ilan, and Thelwall, 2014b) Table 5. Blog post references by cited article publication year (rows) and blog post publication year (columns) Fig.…”
Section: Age Of Cited Articlesmentioning
confidence: 99%
“…Overall, the number of content analysis and qualitative studies on research blogs are limited and only one study (Shema, Bar-Ilan, and Thelwall, 2014b) exists in this area. Most of the altmetric studies also focus on health or basic sciences and rarely deal with social sciences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Young researchers with high presence on Twitter also tend to blog as well and have high networking with similar researchers [11]. Unlike Twitter, blogs are thought to be an effective medium for initiating discourse [12]. A collection of research paper samples from Delicious, Mendeley, Twitter and Wikipedia revealed that 62% of them were present of Mendeley with insignificant presence on other platforms [16].…”
Section: Altmetrics and Related Workmentioning
confidence: 99%